2023
DOI: 10.1002/adfm.202306995
|View full text |Cite
|
Sign up to set email alerts
|

Controllable Electron Distribution Reconstruction of Spinel NiCo2O4 Boosting Glycerol Oxidation at Elevated Current Density

Wenshu Luo,
Han Tian,
Qin Li
et al.

Abstract: Electrocatalytic glycerol oxidation reaction (GOR) is an effective way to convert biomass byproduct to high value‐added chemicals, which; however, suffers from the low oxidation activity and conversion ratio of the presently available catalysts. Herein, the NiCo2O4/NF bimetallic oxide nanoarray is controllably fabricated by Ni substituting for octahedral Co3+ in Co3O4, which exhibits excellent GOR catalytic activity at elevated current densities (E300 = 1.42 V, E600 = 1.62 V) and overall Faradaic efficiency of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(11 citation statements)
references
References 47 publications
0
11
0
Order By: Relevance
“…The comparison of the electrochemical parameters of the glycerol electrolyzer coupled to HER equipped with graphite with other systems equipped with metallic electrodes is illustrated in Table S5. The differences in electrolysis configuration, data collection, and units make comparing our data with the literature difficult, , but we may conjecture about some particular cases. For instance, the cell voltage of ∼1.0 V induces small amounts of carbonyl products at mmol L –1 , which increases with potential in all concentrations investigated here (Figure ), and H 2 is detected starting at 2.0 V of cell voltage (Figure ).…”
Section: Resultsmentioning
confidence: 89%
“…The comparison of the electrochemical parameters of the glycerol electrolyzer coupled to HER equipped with graphite with other systems equipped with metallic electrodes is illustrated in Table S5. The differences in electrolysis configuration, data collection, and units make comparing our data with the literature difficult, , but we may conjecture about some particular cases. For instance, the cell voltage of ∼1.0 V induces small amounts of carbonyl products at mmol L –1 , which increases with potential in all concentrations investigated here (Figure ), and H 2 is detected starting at 2.0 V of cell voltage (Figure ).…”
Section: Resultsmentioning
confidence: 89%
“…Since the first AA electrosynthesis (with a yield of 47%) via NiOOH electrodes under a current density of 6 mA cm –2 , great progress has been made in developing more efficient Ni-based catalysts, such as Ni­(OH) 2 and NiFe LDH. Despite these efforts, the ECO of KA to AA still suffers from low current densities and production rates, limiting its industrial applications. Recently, Co-based spinel oxides, especially Co 3 O 4 , have been employed to promote efficient ECO of small molecules (e.g., 5-hydroxy-methylfurfural, glycerol) due to their unique e g orbital hybridization and rich 3d electron occupancies. Our recent research also found that Co-based catalysts can achieve AA electrosynthesis . However, for pure Co 3 O 4 , its catalytic activity is relatively poor due to its weak adsorption and activation capacity for KA molecules.…”
Section: Resultsmentioning
confidence: 99%
“…Recent research efforts have been centered on the development of highly efficient and cost-effective electrocatalysts for glycerol oxidation reaction (GOR). A notable advancement in this area is the use of bimetallic electrocatalysts, exemplified by NiCo 2 O 4 / NF, investigated by Shi et al 110 This electrocatalyst, syn-…”
Section: Benzyl Alcoholmentioning
confidence: 99%
“…A notable advancement in this area is the use of bimetallic electrocatalysts, exemplified by NiCo 2 O 4 /NF, investigated by Shi et al . 110 This electrocatalyst, synthesized through hydrothermal and calcination processes, featured a distinctive 3D nanoneedle array structure, as shown in Fig. 10a and b.…”
Section: Alcohol Electrooxidation Reactionmentioning
confidence: 99%